An aqueous lithium / sodium ion battery electrolyte with directional ion transport channels
The mixed electrolyte of lithium sulfate, sodium sulfate and sodium dodecyl sulfate form a directional ion transport channel, which solves the problem of insufficient cyclic stability and rate performance of aqueous ion batteries, and achieves high ionic conductivity and environmentally friendly electrolysis Liquid, suitable for improving electrochemical performance of water-based lithium/sodium ion batteries.
Patent Information
- Application Number
- CN202210281726.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-03-21
AI Technical Summary
The cycle stability of existing water-based ion batteries is poor and the rate performance is poor. Especially the classic high-concentration organic lithium electrolyte is unfriendly and has high cost. The ionic conductivity of low-cost electrolyte is low, making it difficult to improve circulation at the same time. Stability and rate performance.
Mixed aqueous solution of lithium sulfate (Li2SO4)-sodium sulfate (Na2SO4)-sodium dodecyl sulfate (SDS) is used as the electrolyte to form a directional ion transport channel, inhibit the reaction activity of water, and maintain high ions at room temperature and low temperature. Conductivity, a one-dimensional conductive channel is formed through the orderly arrangement of SDS micelle clusters.
The cycle stability and rate performance of water-based lithium/sodium ion batteries have been improved. The electrolyte is fluorine-free, environmentally friendly, low-cost, and maintains high ionic conductivity within a wide temperature range, which solves the reduction of water reaction activity in the electrolyte. Dilemma that is difficult to achieve at the same time as the increase in ionic conductivity.
Smart Images

Figure CN114937822B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical energy storage and relates to an aqueous lithium / sodium ion battery electrolyte with a directional ion transmission channel. Background Art
[0002] Ion batteries using organic electrolytes are referred to as organic ion batteries, and ion batteries using aqueous electrolytes are referred to as aqueous ion batteries. Compared with organic ion batteries, aqueous ion batteries have the advantages of being environmentally friendly, having high rate performance, and having no safety hazards, and therefore have received widespread attention (Chem. Soc. Rev. 2020, 49, 180-232). However, due to the dissolution of electrode materials in aqueous electrolytes and their side reactions with aqueous electrolytes, the cyclic stability of aqueous ion batteries is poor (Nat. Chem. 2010, 2, 760-765; Energy Environ. Sci. 2016, 9, 3666-3673).
[0003] In order to improve the cycle stability of aqueous ion batteries, researchers have developed a variety of methods, such as utilizing the conversion and intercalation chemistry of halogen ions (Nature 2019, 569, 245-250), designing new electrode materials and modifying electrode materials (Adv. Energy Mater. 2015, 5, 150100), decoupling electrolytes (Nature Energy 2020, 5, 440-449), adding additives that are conducive to the formation of electrode / electrolyte interfaces (Small 2020, 16, 2003585), removing oxygen from the electrolyte and adjusting the pH of the electrolyte (Nat. Chem. 2010, 2, 760-765), and reducing the amount of free water in the electrolyte (Science 2015, 350, 938-943; Nat. Energy 2016, 1, 16129).
[0004] Recently, researchers have found that the use of "salt-in-water" (a concentrated electrolyte solution) electrolyte can effectively improve the cyclic stability of aqueous ions (Science 2015, 350, 938-943; Nat. Energy 2016, 1, 16129), which is attributed to the strong binding of high-concentration electrolytes with water molecules, reducing the reactivity of water in the electrolyte. The classic "salt-in-water" electrolyte is a high-concentration organic lithium salt (such as LiTFSI, LiBETI, LiOTf), which is not only expensive but also environmentally unfriendly, which limits its practical application (Nat. Energy 2019, 4, 269-280).
[0005] In order to solve this problem, researchers have developed molecular crowding effect electrolytes (Nat. Mater. 2020, 19, 1006-1011), ion polymer water (Nat. Commun. 2018, 9, 5320), local "salt water" (Angew. Chem. Int. Ed. 2021 2021, 60, 19965-19973), and low-cost saturated concentration alkali metal nitrates, sulfates, acetates and formates and other electrolytes (Energy Environ. Sci. 2018, 11, 2876-2883; Chem. Commun. 2019, 55, 12817-12820). The above electrolytes solve the problems of environmental unfriendliness and high cost of high-concentration fluoride electrolytes, but due to their low ionic conductivity, the rate performance of aqueous ion batteries using the above electrolytes is poor. Therefore, exploring new electrolytes with high ionic conductivity and low water reactivity has important scientific significance and application value. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides an aqueous lithium / sodium ion battery electrolyte with a directional ion transport channel, which can simultaneously improve the cycle stability and rate performance of the aqueous lithium / sodium ion battery.
[0007] An aqueous lithium / sodium ion battery electrolyte with a directional ion transport channel, characterized in that the electrolyte is composed of a mixed aqueous solution of lithium sulfate (Li2SO4)-sodium sulfate (Na2SO4)-sodium dodecyl sulfate (SDS), abbreviated as LN-SDS-n.
[0008] The LN-SDS-n, wherein L represents lithium sulfate, N represents sodium sulfate, and SDS is sodium dodecyl sulfate; n represents the concentration of SDS in the electrolyte as a multiple of its critical micelle concentration (cmc). The critical micelle concentration (cmc) of SDS is 8.4 mmol L at room temperature. -1 , the data comes from Biomacromol.2019,20,4361-4369.
[0009] The electrolyte has suppressed reactivity of water, can form a directional ion transport channel at room temperature without an external electric field or at -15 to 0°C with an external electric field, and charge carriers can form a quasi-continuous ion flow in the channel, thereby ensuring high ion conductivity of the electrolyte over a wide temperature range, thereby facilitating improvement of room temperature and low temperature electrochemical performance of aqueous lithium / sodium ion batteries.
[0010] The directional ion transport channel is a channel formed by orderly arrangement of SDS micelle clusters, and the conductive ions are transported in a one-dimensional direction in the channel, rather than the situation where the non-conductive ions or their clusters are randomly distributed.
[0011] The concentration of lithium sulfate and sodium sulfate in the LN-SDS-n is 0.5-1 mol L -1 .
[0012] The LN-SDS-n, wherein n=30-120.
[0013] The LN-SDS-n has an ionic conductivity of 13-93 mS cm at -15°C to room temperature (25°C). -1 .
[0014] The freezing point of the LN-SDS-n is -(3-4)°C.
[0015] The electrochemical stability window (ESW) of the LN-SDS-n is 1.78-2.06 V. The electrochemical stability window is the electrochemical window in which the electrolyte is within and has no hydrogen or oxygen evolution phenomenon.
[0016] Preferably, the LN-SDS-n, wherein n=75-105; further preferably, the LN-SDS-n, wherein n=90.
[0017] Raman spectrum of LN-SDS-n. Figure 3 It can be seen that when n ≥ 30, the spectrum appears at 2800-3000cm -1 The stretching vibration peaks attributed to CH3 and CH2 groups indicate the presence of SDS. Importantly, as n increases from 1 to 90, the peaks at 3000-3800 cm -1 OH stretching vibration peak.
[0018] The low temperature conductivity of LN-SDS-n (n = 30, 60, 90, 120) is very good. At -15℃, the conductivity of LN-SDS-n (n = 30, 60, 90, 120) is 13-17mS cm -1 .
[0019] The preparation method of LN-SDS-n comprises the following steps:
[0020] 1) Use distilled water as solvent to prepare 0.5-1 mol L -1 Li2SO4 and 0.5-1mol L -1 Mixed solution of Na2SO4 VmL, obtain solution A;
[0021] 2) Add SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed solution to obtain LN-SDS-n. The amount of SDS used is 288.38×8.4×n×V / 1000, where 288.38 is the molecular weight of SDS, 8.4 is the cmc of SDS at room temperature, and n=30-120. Sealing is to prevent the electrolyte from absorbing moisture and falling into dust.
[0022] The present invention also provides the use of LN-SDS-n, which is used for the electrolyte of NaTi2(PO4)3||LiMn2O4 (hereinafter referred to as NTP||LMO) aqueous ion battery. NaTi2(PO4)3||LiMn2O4 refers to a battery in which the negative electrode material is NaTi2(PO4)3 (hereinafter referred to as NTP) and the positive electrode material is LiMn2O4 (hereinafter referred to as LMO).
[0023] Beneficial Effects
[0024] 1. The aqueous electrolyte provided by the present invention is fluorine-free, environmentally friendly, low-cost, and easy to mass-produce industrially.
[0025] 2. The aqueous electrolyte provided by the present invention suppresses the reaction activity of water, thereby improving the cycle stability of aqueous lithium / sodium ion batteries.
[0026] 3. The aqueous electrolyte provided by the present invention can form a directional ion transmission channel at room temperature and without an electric field; under the action of an external voltage, it can also form a directional ion transmission channel in the range of zero to minus 15 degrees. The formation of a directional ion transmission channel can enable charge carriers to form a quasi-continuous ion flow in the channel, improve the room temperature and low temperature ion conductivity of the electrolyte, and thus improve the rate performance of aqueous lithium / sodium ion batteries.
[0027] 4. The aqueous electrolyte provided by the present invention solves the dilemma that it is difficult to simultaneously improve the ionic conductivity of the electrolyte and reduce the water reaction activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the LSV curve diagram of LN-SDS-n.
[0029] Figure 2 This is the ESW curve of LN-SDS-n.
[0030] Figure 3 This is the Raman spectrum of LN-SDS-n.
[0031] Figure 4 This is the conductivity curve of LN-SDS-n.
[0032] Figure 5 This is the differential scanning calorimetry curve of LN-SDS-n.
[0033] Figure 6 This is the freezable water content diagram of LN-SDS-n.
[0034] Figure 7 This is the molecular dynamics simulation diagram of LN-SDS-90 at room temperature.
[0035] Figure 8 This is the molecular dynamics simulation diagram of LN-SDS-0 at room temperature.
[0036] Fig. 9 For low temperature applied voltage (2V nm -1 ) under the action of LN-SDS-90 molecular dynamics simulation diagram.
[0037] Fig.10 This is the charge and discharge curve of NTP∥LMO at room temperature and 0.2C.
[0038] Fig.11 This is the rate performance diagram of NTP∥LMO at room temperature.
[0039] Fig.12 This is the cyclic stability diagram of NTP∥LMO at room temperature.
[0040] Fig.13 This is the cycling stability diagram of NTP∥LMO at 0℃, and the electrolyte is LN-SDS-90.
[0041] Fig.14 This is the cycling stability diagram of NTP∥LMO at -15°C, and the electrolyte is LN-SDS-90. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below through specific embodiments in combination with the accompanying drawings. These embodiments are only for illustrating the technical solution of the present invention and cannot be regarded as limiting the content of the claims of the present invention.
[0043] Lithium sulfate, sodium sulfate, sodium dodecyl sulfate, and N-methylpyrrolidone in the examples were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd. TM GF / A glass fiber paper, acetylene black and polyvinylidene fluoride were purchased from Taobao Jinghong New Energy Online Store, stainless steel wire mesh was purchased from Shanghai Xing'an Screen Manufacturing Factory, carbon cloth was purchased from Taiwan Carbon Energy Technology Co., Ltd., BH5510 sulfonated diaphragm was purchased from Shenzhen Gebang Technology Co., Ltd., NTP was homemade according to the reference (J.Alloys Compd.2019,782,576-585), and LMO was purchased from Jining Wujie Technology Co., Ltd.
[0044] Raman spectrum was obtained by Renishaw inVia plus Raman spectrometer; differential thermal analysis was obtained by TA Instruments DSC2500 scanning differential calorimeter; rheological properties were obtained by TA DHR-2 interfacial rheometer; electrochemical properties of LN-SDS-n and NTP∥LMO batteries were obtained by Shanghai Chenhua CHI760E electrochemical analyzer and Wuhan Lanhe CT2001A; theoretical simulation was calculated using GROMACS software package.
[0045] Example 1
[0046] The preparation steps of LN-SDS-0 are as follows:
[0047] Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 Na2SO4 mixed solution 20mL,
[0048] LN-SDS-0.
[0049] Example 2
[0050] The preparation steps of LN-SDS-1 are as follows:
[0051] 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0052] 2) Add 0.048 g SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed solution to obtain LN-SDS-1.
[0053] Example 3
[0054] The preparation steps of LN-SDS-30 are as follows:
[0055] 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0056] 2) Add 1.45 g SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed solution to obtain LN-SDS-30.
[0057] Example 4
[0058] The preparation steps of LN-SDS-60 are as follows:
[0059] 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0060] 2) Add 2.91 g of SDS to solution A, seal the container, stir at room temperature for 10 minutes, and then let it stand until it becomes a transparent, bubble-free mixed solution to obtain LN-SDS-60.
[0061] Example 5
[0062] The preparation steps of LN-SDS-90 are as follows:
[0063] 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0064] 2) Add 4.36 g of SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed liquid to obtain LN-SDS-90.
[0065] Example 6
[0066] The preparation steps of LN-SDS-120 are as follows:
[0067] 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0068] 2) Add 5.81 g of SDS to solution A, seal the container, stir at room temperature for 10 minutes, and then let it stand until it becomes a transparent, bubble-free mixed liquid to obtain LN-SDS-120.
[0069] Results Analysis
[0070] Figure 1 The room temperature linear sweep voltammetry (LSV) diagram of LN-SDS-n. Figure 1 It can be seen that the electrochemical stability window (ESW) of LN-SDS-n (n ≥ 1) is located at 1.78-2.06 V relative to the reversible hydrogen electrode (Table 1), which is greater than 1.72 V of LN-SDS-0. Moreover, as n gradually increases, the ESW gradually increases to 2.06 V for LN-SDS-90 and then decreases to 2.02 V for LN-SDS-120 ( Figure 2 ). This is attributed to the formation of hydrogen bonds between the SDS head group and water molecules, which can reduce the reactivity of water molecules. LSV results show that the directional dynamics of water molecules in LN-SDS-n and the hydrogen bonds between the SDS head group and water molecules do not have a linear dependence on the SDS concentration.
[0071] Table 1 Room temperature ESW of different electrolytes
[0072]
[0073] Raman spectroscopy can reflect the reactivity of water molecules in the system. Figure 3 is the Raman spectrum of LN-SDS-n. Figure 3 It can be seen that when n ≥ 30, the spectrum appears at 2800-3000cm -1 The stretching vibration peaks attributed to CH3 and CH2 groups indicate the presence of SDS. Importantly, as n increases from 1 to 90, the peaks at 3000-3800 cm -1 The OH stretching vibration peak of LN-SDS-90 gradually decreases in intensity, while the OH stretching vibration peak intensity increases when n increases from 90 to 120. Raman spectroscopy results show that the reactivity of water in LN-SDS-90 is the lowest, which is consistent with the results of LSV.
[0074] The ionic conductivity of LN-SDS-n at room temperature to -15°C was measured and calculated using electrochemical impedance spectroscopy. Figure 4 ).Depend on Figure 4 It can be seen that the conductivity of LN-SDS-n (n = 60, 90, 120) is significantly higher than that of LN-SDS-0 and LN-SDS-30, and is also significantly higher than that of the classic 21m LiTFSI "salt-in-water" electrolyte ( Figure 4 21 m LiTFSI was used for comparison). In addition, the room temperature conductivity of LN-SDS-n (n = 30, 60, 90, 120) (50-93 mS cm -1 ), which is comparable to 10-40m HCOOK, 10-30m KOAc and 25mLiNO3, and higher than other low-cost “salt-in-water” and molecular crowding effect organic fluoride electrolytes (Table 2).
[0075] Table 2 Comparison of room temperature ionic conductivity of different electrolytes
[0076]
[0077] Importantly, the low temperature conductivity of LN-SDS-n (n = 30, 60, 90, 120) is excellent. For example, at -15°C, the conductivity of LN-SDS-n (n = 30, 60, 90, 120) is 13-17 mS cm -1 , while the conductivity of 25m LiNO3 at 10℃ is only 0.016mS cm -1 (Angew. Chem. Int. Ed. 2021, 60, 19965-19973), there is no data reported for 25m LiNO3 at sub-zero temperatures. As the temperature decreases, the conductivity decreases, which is a general rule. Therefore, below zero degrees Celsius, the conductivity of LN-SDS-n (n = 30, 60, 90, 120) is much higher than that of 25m LiNO3.
[0078] Among LN-SDS-n (n=30, 60, 90, 120), LN-SDS-90 has the highest conductivity at different temperatures. This is because as n increases, the charge carrier concentration in the electrolyte increases, but the viscosity of the electrolyte also increases at the same time. Compared with LN-SDS-90, the lower conductivity of LN-SDS-120 is attributed to the increase in system viscosity, resulting in the binding effect of SDS micelles on cations exceeding the contribution of the increase in charge carrier concentration to conductivity.
[0079] The content of freezable water in aqueous electrolyte is an important indicator for evaluating its low-temperature (≤0℃) operation reliability. Figure 5 The LN-SDS-n differential scanning calorimetry curve is given. Figure 5 It can be seen that as n increases by 30, the freezing point of the electrolyte decreases from -2.52°C of LN-SDS-0 to -4.03°C; and then as n increases, the freezing point of the electrolyte gradually increases to -3.07°C of LN-SDS-120. This shows that the addition of SDS is beneficial to lowering the freezing point of the electrolyte, but the decrease in the freezing point is not linearly related to the increase in SDS concentration. In addition, sodium sulfate and lithium sulfate in the system make important contributions to lowering the freezing point of the electrolyte. For example, the freezing point of SDS-90 (the electrolyte does not contain lithium sulfate and sodium sulfate, and the concentration of SDS is 90cmc) is -0.35°C, which is significantly higher than -3.71°C of LN-SDS-90. Therefore, the decrease in the freezing point of LN-SDS-n is attributed to the reaction between SDS and Li + / Na + and SO4 2- The synergistic effect of Figure 5 The data can be used to calculate the content of freezable water in the electrolyte. Figure 6 As shown, the variation trend of the freezable water content in LN-SDS-n is consistent with its freezing point; that is, the lower the freezable water content, the lower the freezing point of the electrolyte.
[0080] Although the freezing point of LN-SDS-n is not lower than -4.03℃, LN-SDS-n (n=30,60,90,120) still has high ionic conductivity at -15℃. To explain this experimental result, we performed molecular dynamics simulation using LN-SDS-90 as an example. The simulation results show that the SDS micelle clusters in LN-SDS-90 at room temperature are orderly arranged to form a directional ion transport channel ( Figure 7 ), while in LN-SDS-0, ions are randomly distributed in the electrolyte in the form of clusters at room temperature and cannot form qualitative ion transport channels ( Figure 8 ). At low temperature (-15-0℃), SDS and Li in LN-SDS-90 + / Na + and SO4 2- Ions are randomly distributed, and no directional ion transport channel is formed; under the action of electric field (0.5-2V nm -1 ), the SDS micelle clusters in LN-SDS-90 are orderly arranged to form a qualitative ion transport channel, and the charge carriers form a quasi-continuous ion flow in the channel ( Fig. 9 ), which ensures the high ionic conductivity of LN-SDS-90 at low temperatures.
[0081] Table 3 NTP∥LMO aqueous ion electrolyte, separator, and current collector type
[0082]
[0083] Example 7
[0084] Assembly of NTP∥LMO aqueous ion battery:
[0085] 1) Take appropriate amount of electrode material powder, acetylene black and polyvinylidene fluoride (mass ratio 8:1:1), transfer them to an agate mortar, add appropriate amount of N-methylpyrrolidone, grind them thoroughly, and prepare slurry; the electrode material powder includes NTP powder and LMO powder; prepare NTP working electrode with NTP electrode material powder, and prepare LMO working electrode with LMO electrode material powder.
[0086] 2) The slurry was evenly coated on the current collector, and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a working electrode.
[0087] 3) With NTP working electrode as negative electrode, LMO working electrode as positive electrode, LN-SDS-n as electrolyte, and separator between positive and negative electrodes, R2032 button cell was assembled. Specific conditions are shown in Table 3.
[0088] Results Analysis
[0089] Fig.10 LN-SDS-n is used as the electrolyte, NTP∥LMO is at room temperature 0.2C (1C = 133mAg -1 ) under the charge and discharge curve. Fig.10 It can be seen that when n is equal to 0, 1, 30, 60, 90, and 120, the discharge specific capacities of NTP∥LMO are 59.4, 67.1, 62.8, 60.9, 65.1, and 55.6 mAh g, respectively. -1 . Importantly, with LN-SDS-n (n ≥ 1) as the electrolyte, the coulombic efficiency of NTP∥LMO charging and discharging is significantly improved, which means that LN-SDS-n (n ≥ 1) can improve the reversibility of the electrode reaction. In addition, compared with LN-SDS-n (n = 0, 1, 30, 120), with LN-SDS-60 and LN-SDS-90 as the electrolyte, the discharge specific capacity of NTP∥LMO at different current densities is significantly improved, and it still has a high discharge specific capacity at 5C ( Fig.11 ). This shows that LN-SDS-60 and LN-SDS-90 can improve the rate performance of NTP∥LMO.
[0090] Fig.12 is the room temperature cycling stability diagram of NTP∥LMO. Fig.12 It can be seen that with LN-SDS-0 as the electrolyte, NTP∥LMO was cycled 600 times at 1C, and the discharge specific capacity was 17.1mAg -1 , the capacity retention rate is only 26.9%. However, with LN-SDS-n (n=60, 90, 120) as the electrolyte, the NTP∥LMO discharge specific capacities are 40.5, 47.1 and 28.4 mA g-1 after 600 cycles of charge and discharge at 1C, 200 cycles at 2C, 400 cycles at 5C, and 800 cycles at 1C, for a continuous charge and discharge cycle of 2000 cycles. -1 , and the corresponding capacity retention rates are 61.9%, 70.4% and 66.2%, respectively. It can be seen that LN-SDS-n (n = 60, 90, 120) can significantly improve the electrochemical cycling stability of NTP∥LMO.
[0091] Fig.13 The cyclic stability diagram of NTP∥LMO at zero degrees with LN-SDS-90 as the electrolyte. Fig.13 It can be seen that after 600 cycles at 1C, 1000 cycles at 2C, 2000 cycles at 5C, 1000 cycles at 2C, and 400 cycles at 1C, the NTP∥LMO discharge capacity is 35.2 mA g -1 , the capacity retention rate is 93.1%. Even at -15℃, 200 cycles at 1C, 200 cycles at 2C, 600 cycles at 1C, and 1000 cycles continuously, the NTP∥LMO discharge capacity is 10.7mAg-1 , the capacity retention rate is 71.3% ( Fig.14 ), showing excellent low temperature cycling stability.
[0092] In summary, the present invention provides an aqueous lithium / sodium ion battery electrolyte with a directional ion transport channel, in which the reactivity of water molecules is suppressed, and the electrolyte has a high ionic conductivity in the range of room temperature to minus 15°C, which effectively solves the dilemma faced by aqueous electrolytes, because it is difficult to simultaneously reduce the reactivity of water in the electrolyte and increase the ionic conductivity. The present invention also provides the use of the electrolyte, namely, for the assembly of aqueous NTP∥LMO ion batteries, and the NTP∥LMO based on the electrolyte exhibits excellent room temperature and low temperature electrochemical properties.
Claims
1. An aqueous lithium / sodium ion battery electrolyte LN-SDS-n with directional ion transport channels, characterized in that: The electrolyte is composed of a mixed aqueous solution of lithium sulfate-sodium sulfate-sodium dodecyl sulfate (SDS), wherein the concentration of lithium sulfate and sodium sulfate in the LN-SDS-n is 0.5-1 mol L -1 The amount of SDS is 288.38×8.4×n×V / 1000, where 288.38 is the molecular weight of SDS, and 8.4 is the cmc of SDS at room temperature. The LN-SDS-n, wherein L represents lithium sulfate, N represents sodium sulfate, and SDS is sodium dodecyl sulfate; n represents the concentration of SDS in the electrolyte as a multiple of its critical micelle concentration (cmc); wherein n=90; A directional ion transport channel can be formed at room temperature without an external electric field or at -15 to 0°C with an external electric field. The LN-SDS-n has an ionic conductivity of 13-93 mS cm at -15°C to room temperature (25°C). -1 ; At -15°C, the conductivity of LN-SDS-n (n=30-120) is 13-17 mS cm -1 ; The LN-SDS-n has a freezing point of -(3-4)°C; The LN-SDS-n has an electrochemical stability window (ESW) of 1.78-2.06V; The aqueous lithium / sodium ion battery electrolyte LN-SDS-n is used as the electrolyte of NaTi2(PO4)3||LiMn2O4 aqueous ion battery.
2. The electrolyte LN-SDS-n according to claim 1, characterized in that The Raman spectrum of LN-SDS-n showed a peak at 2800-3000 cm -1 The stretching vibration peaks attributed to CH3 and CH2 groups are located at 3000-3800cm -1 OH stretching vibration peak.
3. The method for preparing LN-SDS-n according to claim 1 or 2, comprising the following steps: 1) Use distilled water as solvent to prepare 0.5-1 mol L -1 Li2SO4 and 0.5-1mol L -1 Mixed solution of Na2SO4 V mL, solution A is obtained; 2) Add SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed liquid to obtain LN-SDS-n; the amount of SDS used is 288.38×8.4×n×V / 1000, wherein 288.38 is the molecular weight of SDS, 8.4 is the cmc of SDS at room temperature, and n=90.
